Performance Evaluation of Maxy Academy Learning Management System (LMS) Implementation Using the Task Technology Fit (TTF) Method: Evaluasi Kinerja Implementasi Learning Management System (LMS) Maxy Academy Menggunakan Metode Task Technology Fit (TTF) - Napitupulu, Virelle Rachel Caroline; Palupi, Ghea Sekar (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
Information technology today has changed many aspects of daily life, one of which is in the field of education. One of the applications that support this is Maxy Academy's Learning Management System. Maxy Academy LMS is a system used for learning in terms of online skill development. The goal of the company is to provide opportunities for individuals to improve their knowledge and skills through a structured curriculum and experienced infrastructure. This study aims to determine the success rate of Maxy Academy LMS implementation using the Task Technology Fit (TTF) method. From the results of the distribution of respondents, 333 respondents were obtained and the data preprocessing stage was carried out so that the remaining 273 respondents were processed. The results showed that all variables in this study had a significant effect. But the Task Technology Fit variable has a weak R-Square value of 0.224. So the recommendations that can be given by Maxy Academy LMS can provide the latest and detailed content, provide convenience for users in terms of information, and maintain user data and evaluation results more carefully.